2015
DOI: 10.1016/j.jpeds.2014.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Fontan-Associated Protein-Losing Enteropathy and Plastic Bronchitis

Abstract: Objective Characterize the medical history, disease progression, and treatment of current-era patients with the rare diseases Fontan-associated protein losing enteropathy (PLE) and plastic bronchitis (PB). Study Design A novel survey that queried demographics, medical details, and treatment information was piloted and placed online via a Facebook portal allowing social media to power the study. Participation regardless of PLE or PB diagnosis was allowed. Case control analyses compared patients with PLE and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 25 publications
6
62
0
Order By: Relevance
“…The survey questions were not validated prior to distribution, and therefore, interpretation of the questions across respondents may have varied. Social media is increasingly utilized as a tool to facilitate clinical research and has distinct advantages in the study of rare diseases . The large number of responses to our survey likely would not have been possible without harnessing the power of social media to reach the population of interest.…”
Section: Discussionmentioning
confidence: 99%
“…The survey questions were not validated prior to distribution, and therefore, interpretation of the questions across respondents may have varied. Social media is increasingly utilized as a tool to facilitate clinical research and has distinct advantages in the study of rare diseases . The large number of responses to our survey likely would not have been possible without harnessing the power of social media to reach the population of interest.…”
Section: Discussionmentioning
confidence: 99%
“…While survival has previously been reported at 50% at 5‐years, newer studies have shown that survival closer to 80% at 8 years is possible . Newer treatment options such as thoracic duct ligation and transcatheter selective lymphatic embolization have been developed and may be beneficial in refractory cases . Finally, thromboembolism, bleeding, renal dysfunction, and obesity are other complications of Fontan physiology that can adversely affect long‐term outcomes …”
Section: Long‐term Outcomes (Robert Elder Md)mentioning
confidence: 99%
“…1,4 There are many similarities to plastic bronchitis (PB) which occurs in 4-14% of Fontan patients and may present by itself or in combination with PLE. 5,6 Several medical and surgical strategies have been employed to treat PLE and PB, all with variable but modest degrees of success. 1,4,7,8 The role of the lymphatic system has been largely ignored in the management of the failing Fontan.…”
Section: Introductionmentioning
confidence: 99%